2005
DOI: 10.1070/qe2005v035n08abeh009181
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon electron transfer between quantum dots

Abstract: One of the most striking features found in the cosmic microwave background data is the presence of an anomalous cold spot (CS) in the temperature maps made by the Wilkinson Microwave Anisotropy Probe (WMAP). This CS has been interpreted as the result of the presence of a collapsing texture, perhaps coming from some early universe grand unified theory (GUT) phase transition. In this work we propose an alternative explanation based on a completely different kind of texture which appears in a natural way in a bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Similar effects accompany the resonant electron transfer between quantum dots produced by the mechanisms described in works [7,10,11]. Nanocluster formation of the described type in a field of nonresonant wave takes place in the diversified systems from quantum dots, but it is rather inconvenient in ordinary atom-molecular systems -the effect essentially depends on the sizes of quantum dots and distance between them.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Similar effects accompany the resonant electron transfer between quantum dots produced by the mechanisms described in works [7,10,11]. Nanocluster formation of the described type in a field of nonresonant wave takes place in the diversified systems from quantum dots, but it is rather inconvenient in ordinary atom-molecular systems -the effect essentially depends on the sizes of quantum dots and distance between them.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, an electron transfer between levels of identical quantum dots at one-photon resonance was considered in [1][2][3][4][5][6][7][8], and [9][10][11][12] treated transfer processes at a combinational and two-photon resonance between discrete levels of an electron system of two quantum dots with essentially different energies. In [13] the case is considered when the levels relating to two different but not necessary identical quantum dots possess approximately similar energy, and it was shown that the system is enough to be affected by electromagnetic field with only one carrier frequency for an electron transfer between quantum dots, and it is not obligatory for any resonance condition to be obeyed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation